Splat formation and microstructure development during plasma spraying: deposition temperature effects - Sampath, S; Jiang, X (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 1999)
It has been observed that substrate temperature has a dramatic effect in modifying the morphology of splats formed by impacting molten droplets on substrates during plasma spraying. This effect also has important implications on the deposit microstructure and properties. With an increase of substrate temperature from room temperature to a few hundred degrees (200-400 deg C), the splashing tendency is reduced and the splat morphology changes from fragmented to a contiguous disc-shape. Consequently, deposit microstructural integrity improves, and a number of properties are significantly enhanced with concomitant implications for coating performance. The mechanism of this splat morphology change has been subject of considerable investigation within the thermal spray community. It has been suggested by various researchers that the cause of this effect can be attributed to a number of factors such as: a higher solidification rate at the low substrate temperature; poor wetting and/or a contaminated substrate surface at lower temperatures etc. This paper summarizes, the experimental findings and reviews the various proposed hypotheses. The results are synthesized based on some recent experimental findings. Materials studied include molybdenum.